Potential of Nematophagous Fungi from Kutalimbaru, North Sumatra, Indonesia, as Biological Control Agents to Manage Root Knot Nematodes, Meloidogyne incognita - Simanjuntak, Wira Risa Lina; Hastuti, Liana Dwi Sri; Yurnaliza, Yurnaliza (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2025)
Root-knot nematodes (RKN), especially Meloidogyne incognita, are one of the most damaging and widespread plant-parasitic nematodes (PPNs) in cultivated plants worldwide. The intensive application of chemical nematicides in controlling these pests raises environmental and ecological concerns, prompting the need for sustainable alternatives. This study aimed to isolate and evaluate the predatory potential of indigenous nematode-trapping fungi (NTF) from the rhizosphere soils of healthy tomato plants against M. incognita under in vitro conditions. Soil samples were processed using the soil sprinkle technique, and fungal isolates capable of forming traps were screened by exposing them to second-stage juvenile (J2) of M. incognita. This study isolated 20 nematophagous fungi that have antagonistic activity against M. incognita from the rhizosphere soil of tomato plants. Among these, four isolates were identified as nematode-trapping fungi, with TRK 04 showing the highest predation efficacy, followed by TRK 07, TRK 09, and TRK 16. All four isolates were identified as part of the Arthrobotrys genus. These findings highlight the potential of indigenous nematophagous fungi as sustainable biocontrol agents for managing root-knot nematodes. Their application could support the development of environmentally friendly agricultural practices and reduce reliance on chemical nematicides. Further, in vivo studies are recommended to validate their efficacy under field conditions.